TDR (The MIT Press, 2014)
Vol. 61, No. 2 (T234), Summer 2017Edisi kali ini memuat beberapa artikel, diantaranya: Paso Libre: border enactment, infrastucture, and crisis resolution at the port of laredo 1954-1957 (hal. 11). Fragments of the European Refugee Crisis: performing displacement and the re-shaping of greek identity (hal. 32). A Traveling Script: labor migration, precarity, and performance (hal. 48). Memoryscapes of Race: black radial parading cultures of New Orleans (hal. 71). No More Bystanders: grandchildren of Hiroshima and the 70th anniversary of the atomic bomb (hal. 87). A Stage Presence: Michael Kirby’s embedded sculptures (hal. 105). Choreographing Freedom: mass performance in the festivals of the French revolution (hal. 117).